(untitled) (Architecture Image Studies, 2025)
Dong architecture is an important carrier of intangible cultural heritage. Its unique spatial structure and construction technology system contain profound cultural value. At present, faced with the realistic dilemma of traditional construction techniques being on the verge of being lost, cultural inheritance experiencing gaps, and the natural environment being damaged, effective protection paths need to be explored. This study proposes to use building information model and digital technology as the core to construct a visual protection model of Dong buildings, give full play to its advantages of information integration and three-dimensional visualization, and open up new ways for the digital protection of Dong buildings. The research carried out a systematic analysis around four key elements: information expression of cultural semantics, parametric modeling of wooden construction techniques, experience design of interactive communication, and collaborative sharing of multiple subjects, and then proposed a visualization strategy that integrates "modelling-protection-display-dissemination". This research aims to build a complete digital protection system for Dong architectural culture, provide systematic theoretical support and feasible technical solutions for the full-cycle digital inheritance of Dong architectural culture, and promote the digital protection and innovative inheritance of Dong architectural intangible cultural heritage.